2012
DOI: 10.2478/v10078-012-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Introducing a Smaller and Lighter Basketball on Female Basketball Players' Shot Accuracy

Abstract: Our study examined whether the introduction of a smaller and lighter basketball (no. 6) affected the accuracy of female basketball players’ shots at the basket. The International Basketball Federation (FIBA) introduced a size 6 ball in the 2004/2005 season to improve the efficiency and accuracy of technical elements, primarily shots at the basket. The sample for this study included 573 European female basketball players who were members of national teams that had qualified for the senior women’s European champ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Theoretically, the shooting precision could be influenced by the slightly smaller basketball used by men in 3 × 3 basketball; however, in some previous research, it was shown that small differences in ball size and weight do not affect precision of basketball shooting. 21…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the shooting precision could be influenced by the slightly smaller basketball used by men in 3 × 3 basketball; however, in some previous research, it was shown that small differences in ball size and weight do not affect precision of basketball shooting. 21…”
Section: Discussionmentioning
confidence: 99%
“…As points in basketball are scored by putting the ball through the basket, shot success is a logical measure for analyzing efficiency ( Simovic et al, 2012 ). Technical-tactical aspects of shooting actions, however, are not easy to analyze ( Podmenik et al, 2012 ), as they are influenced by complex, interacting factors ( Courel et al, 2013 ; Maszczyk et al, 2014 ; Marmarinos et al, 2016 ; Ozakaki and Rodacki, 2012). Attempts have been made to break down this complexity by studying aspects of the game preceding a successful or unsuccessful shot, such as fast breaks ( Refoyo et al, 2009 ), space-time coordination dynamics ( Bourbousson et al, 2010 ), network metrics (Fewel et al, 2012), and interactions between attackers and defenders ( García et al, 2013a ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there is little research that addresses the rule changes in basketball. Podmenik et al (2012) analyzed shot accuracy of female basketball players before and after a smaller and ligher basketball was introduced in the 2004/05 season (a size 6 ball was introduced instead of a size 7). They did not find any significant differences in field-goal accuracy, but found a significant decrease in free-throw accuracy.…”
Section: Introductionmentioning
confidence: 99%